Answers

2016-06-27T20:44:50+08:00
A^2+b^2+c^2
a raised to the second power + raised to the second power + c raised to the second power
0
2016-06-27T20:47:23+08:00
(a+b+c)(a+b+c) or (a+b+c)² = {(a+b)+c}²
                                            = (a+b)² + 2(a+b)+c + c²
                                            =(a²+2ab+b²) +(2ac+2bc) +c²
                                            =a²+ 2ab+ b² +2ac+ 2bc+ c²
                                            =a²+b²+c²+ 2ab+ 2bc + 2ca

-Hope it will help you...
0